2010
DOI: 10.3109/00016341003801623
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum sexual function of women and the effects of early pelvic floor muscle exercises

Abstract: Pelvic floor-muscle training improves pelvic floor-muscle function, and starting after the puerperal period, exercise appears to have positive effects on female sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
1
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(98 citation statements)
references
References 19 publications
5
79
1
13
Order By: Relevance
“…It remains unclear whether dyspareunia causes muscle changes or whether VRP, PFM strength and endurance may cause dyspareunia. To date, only 1 RCT has investigated effect of PFM training on symptoms of dyspareunia [28]. This study found no statistically significant difference between the group exercising their PFM and the control group.…”
Section: Discussionmentioning
confidence: 41%
“…It remains unclear whether dyspareunia causes muscle changes or whether VRP, PFM strength and endurance may cause dyspareunia. To date, only 1 RCT has investigated effect of PFM training on symptoms of dyspareunia [28]. This study found no statistically significant difference between the group exercising their PFM and the control group.…”
Section: Discussionmentioning
confidence: 41%
“…Other authors observed that PFM function improvement using perineal exercise postpartum (21) or surgical procedure performed to pelvic floor dysfunctions can improve the sexual function (22). In our series, there was no statistical correlation between PFM strength and orgasm.…”
Section: Discussioncontrasting
confidence: 47%
“…However, sexual function was the primary outcome measure in only 1 study done by Citak et al (21), which showed a significant improvement in total FSFI and orgasm domain scores at 7 months postpartum after receiving 3 months of PFM training. In the Citak study, scores of arousal, lubrication, and pain domains were higher in the intervention group than in the control group, however, the differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%